2023
DOI: 10.3390/v15112214
|View full text |Cite
|
Sign up to set email alerts
|

Global Prevalence and Hemagglutinin Evolution of H7N9 Avian Influenza Viruses from 2013 to 2022

Qianshuo Liu,
Haowen Zeng,
Xinghui Wu
et al.

Abstract: H7N9 avian influenza viruses have caused severe harm to the global aquaculture industry and human health. For further understanding of the characteristics of prevalence and hemagglutinin evolution of H7N9 avian influenza viruses, we generated the global epidemic map of H7N9 viruses from 2013 to 2022, constructed a phylogenetic tree, predicted the glycosylation sites and compared the selection pressure of the hemagglutinin. The results showed that although H7N9 avian influenza appeared sporadically in other reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…According to the statistical data of World Health Organization, seasonal influenza epidemics cause an estimated 3 to 5 million cases of severe cases worldwide, resulting in approximately 500,000 deaths, and causing significant economic losses and social burdens ( Eichberg et al, 2022 ). H7N9 influenza virus, an emerging zoonotic pathogen, has led to 1, 564 laboratory-confirmed cases of human infection from its initial outbreak until October 2017, and there are still sporadic infections now ( Liu et al, 2023 ). Hu et al reported that A. muciniphila improved host defense against influenza virus H7N9 infection ( Hu et al, 2021 ).…”
Section: Akkermansia Muciniphila and Infection Related Diseasesmentioning
confidence: 99%
“…According to the statistical data of World Health Organization, seasonal influenza epidemics cause an estimated 3 to 5 million cases of severe cases worldwide, resulting in approximately 500,000 deaths, and causing significant economic losses and social burdens ( Eichberg et al, 2022 ). H7N9 influenza virus, an emerging zoonotic pathogen, has led to 1, 564 laboratory-confirmed cases of human infection from its initial outbreak until October 2017, and there are still sporadic infections now ( Liu et al, 2023 ). Hu et al reported that A. muciniphila improved host defense against influenza virus H7N9 infection ( Hu et al, 2021 ).…”
Section: Akkermansia Muciniphila and Infection Related Diseasesmentioning
confidence: 99%